ARHGEF9 disease: Phenotype clarification and genotype-phenotype correlation. (June 2017) - Alber, Michael; Kalscheuer, Vera M.; Marco, Elysa; Sherr, Elliott; Lesca, Gaetan; Till, Marianne; Gradek, Gyri; Wiesener, Antje; Korenke, Christoph; Mercier, Sandra; Becker, Felicitas; Yamamoto, Toshiyuki; et al.
Abstract : Objective: We aimed to generate a review and description of the phenotypic and genotypic spectra of ARHGEF9 mutations. Methods: Patients with mutations or chromosomal disruptions affecting ARHGEF9 were identified through our clinics and review of the literature. Detailed medical history and examination findings were obtained via a standardized questionnaire, or if this was not possible by reviewing the published phenotypic features. Results: A total of 18 patients (including 5 females) were identified. Six had de novo, 5 had maternally inherited mutations, and 7 had chromosomal disruptions. All females had strongly skewed X-inactivation in favor of the abnormal X-chromosome. Symptoms presented in early childhood with delayed motor development alone or in combination with seizures. Intellectual disability was severe in most and moderate in patients with milder mutations. Males with severe intellectual disability had severe, often intractable, epilepsy and exhibited a particular facial dysmorphism. Patients with mutations in exon 9 affecting the protein's PH domain did not develop epilepsy. Conclusions: ARHGEF9 encodes a crucial neuronal synaptic protein; loss of function of which results in severe intellectual disability, epilepsy, and a particular facial dysmorphism. Loss of only the protein's PH domain function is associated with the absence of epilepsy.